Pengaruh Debt To Equity Rasio (DER) Current Ratio (CR) Terhadap Return On Assets (ROA) : Studi Kasus Pada Perusahaan Retail Yang Terdaftar Di Bursa Efek Indonesia Tahun Periode 2019-2023 - Muhammad Zaenul Firdaus; Evan Damar Yuwanda; Fadhlun Ainul Kirom (Journal of Research and Publication Innovation, 2025)
This study aims to determine whether there is an effect of Debt to Equity Ratio (DER) on Return on Assets (ROA) and Current Ratio (CR) on Return on Assets (ROA) and the simultaneous effect of Debt to Equity Ratio (DER) & Current Ratio (CR) on Return on Assets in retail companies listed on the Indonesia Stock Exchange. The data sample for this study was obtained from annual financial reports from 6 retail companies during the 2019-2023 period. The data testing technique in STATA uses the Chow Test, Haussman Test and LM Test. Analysis of the methods used Classical Assumption Test, Heteroscedasticity Test, Panel data regression equation, T Test & F Test. The results of this study indicate that the partial results of the t test on the DER variable (X1) obtained a t count value of -0.41 <t table 2.05 and a sig value of 0.681> 0.05, then Ha is rejected and H0 is accepted, meaning that the DER variable does not affect ROA in the case study in retail companies listed on the Indonesian stock exchange. The results of the t test on the CR variable (X2) obtained a t count value of -0.93 <t table 0.05 and a sig value of 0.359> 0.05, then Ha is rejected and H0 is accepted, meaning that the CR variable does not affect ROA in the case study in retail companies listed on the Indonesian stock exchange. The F count value is 0.44 <F table 3.55 and the sig value. That is 0.6505 > 0.05, then Ha is rejected and H0 is accepted, meaning that the DER and CR variables do not affect ROA in the case study of retail companies listed on the Indonesian Stock Exchange.